What Turns Task Crafters into High Performers? Affective Commitment and Strategic Alignment as Critical Levers - Inyong Shin; Jong Gyu Park; Heesun Chae (Behavioral Sciences)
Considering that the impacts of task crafting on task performance are not uniform and may depend on goal congruence, this study attempted to explore the roles of affective commitment in individual–organizational goal congruence and strategic alignment in job–organizational goal congruence. Drawing on conservation of resources theory, we anticipated that affective commitment as a motivational resource and strategic alignment as an organizational resource would be critical levers for task crafting to affect task performance. Using a time-lagged design with two data-collection points, we conducted a multilevel analysis of data from 138 subordinates and 50 supervisors. As a result, we found that task crafting had the strongest positive effect on task performance when both affective commitment and strategic alignment were high. This study offers new insights regarding task crafting by identifying how employees can be effectively proactive. It also expands the theoretical application of conservation of resources theory by specifying how different types of resources interact to improve performance.